Pengaruh Bahasa Ibu (Interferensi) Terhadap Kesalahan Tulisan (Kitabah) Mahasiswa Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam Sunan Pandanaran Yogyakarta - Muhammad Rifa’i; Faqih Ahmad; Iftitah Izza Farhani; Alam Budi Kusuma (STAI Masjid Syuhada Yogyakarta, 2024)
Foreign language learners, including Arabic, are often influenced by the language of their mother tongue. In phonology, syntax and morphology between Indonesian and Arabic there are very significant differences. Likewise in the realm of language structure. This difference is often a factor that makes it difficult for Arabic language learners to express their ideas in the form of a kitabah (writing). This allows interference in Indonesian, which is the mother tongue for students of the Arabic Language Education Study Program at STAI Sunan Pandanaran Yogyakarta, with their skills in the field of maharah kitabah (writing skills) which causes errors in writing Arabic. This research is field research with a qualitative descriptive nature. Data was obtained through observation, questionnaires and documentation. The questionnaire produces data in the form of students' writing in Arabic which reaches 70% of the research subject population. The writing was then analyzed for what forms of mother tongue interference there were with students' Arabic writing errors and what factors were behind the interference. Indonesian grammar which always places the subject before the predicate results in language interference which results in errors in writing Arabic in the Total Fi'liyyah pattern which puts the predicate before the subject. Cultural interference occurs in adapting the pattern or form of the khabar to its mubtada', as well as the translation of the word 'mother' which is already represented by the isim muannats. Semantic Interference occurs when errors in selecting jar letters that do not match their meaning. Then morphological interference occurs in adjusting the shape of the fi'il to its mubtada'.